Behavior Of Flowable High Strength Concrete Repair Material For Sustainable Engineering Construction - Ramli, Mahyuddin; Th. Dawood, Eethar (2008)

(untitled)
Steel fibers in concrete is known for its potential ability to enhance the concrete material for increasing their flexural toughness, energy dissipation and have high impact resistance for many structural applications especially in building repairs and other civil engineering works.